Early simultaneous bilateral total hip arthroplasty for the management of bilateral acetabular fracture in an elderly patient - Christine Tempelaere, MD; Pierre Diviné, MD; Thierry Bégué, MD, PhD (Arthroplasty Today, 2019)
Bilateral acetabular fractures in elderly patients due to seizures are very rare and management is a challenge. The standard treatment for acetabular fracture, open reduction with internal fixation, is not recommended for the elderly because of poor bone quality and the need for bed rest. In the acute phase, total hip arthroplasty may be the best treatment option because it allows early mobilization and avoids bed rest complications. We report the case of a 76-year-old man with a bilateral comminuted acetabular fractures and a left fracture dislocation of the shoulder, treated by immediate shoulder arthroplasty and a one-stage bilateral total hip arthroplasty procedure at 3 weeks, with a good result at 1-year follow-up. Keywords: Simultaneous bilateral total hip arthroplasty, Epilepsy, Bilateral acetabulum fracture